Biological determinants outweigh the learning environment: a path-analytic model of physical fitness, nutritional status, and motor ability in primary-school children - Ridho Guswandi; Masrun Masrun; Khairuddin Khairuddin; Donie Donie (IICET (Indonesian Institute for Counseling, Education and Therapy), 2026)
Motor skills in the middle childhood phase are a critical skill through which one could attain lifelong physical activity; However, their determinants are often examined separately, which